Physical exercise improves body weight gain and liver function in malnourished rats without disturbing the redox balance - Cruz de OLIVEIRA, Emerson; Cardoso dos SANTOS, Rinaldo; Kappes BECKER, Lenice; Barbosa COELHO, Daniel; PEDROSA, Maria Lúcia; Eustáquio SILVA, Marcelo (Revista de Nutrição, 2023)
Objective To study the relationship between exercise and malnourishment because recent evidence suggests that exercise can cause the benefi cial adaptation of antioxidant systems, whereas malnourishment can cause harmful adaptation of these systems. Methods Thirty-two female Fischer rats were equally divided into Sedentary Control, Trained Control, Sedentary Malnourished and Trained Malnourished groups. The training protocol consisted of swimming for 30 minutes continuously for 5 days/week for 8 weeks. Results It was demonstrated that aspartate aminotransferase and alanine aminotransferase activities increased in malnourished rats, but physical training reversed these effects by lowering the raised levels. The glutathione level was diminished by malnourishment whereas physical training increased the levels of liver carbonyl protein and increased the levels of thiobarbituric acid reactive substances that were diminished by malnourishment. In addition, Trained Malnourished rats had a higher average body weight than Sedentary Malnourished ones (62.77g vs. 55.08g, respectively). Conclusion The data show that exercise was able to reverse or reduce damage caused by malnourishment, such as weight loss and liver dysfunction by a pathway independent of the participation of enzymes involved in antioxidant defense and that there is no interaction between exercise and malnutrition.